Pembuatan Lembar Kerja Peserta Didik Interaktif Berbasis Google Form Bagi Mahasiswa PSGD - Bagas Oktobera Sanyata; Delta Ramawati; Titin Sulistyowati; Putri Zudhah Ferryka (CV. ITTC INDONESIA, 2024)
The background to the community service activities that we carry out is because there are still some students who do not understand how to create interactive student worksheets based on Google Forms. This community service is carried out in the form of training in making interactive student worksheets using Google Forms using the discovery learning learning model. This activity aims to improve skills and understanding in creating interactive student worksheets. The method used is CBR (Community Based Research). This activity is a collaboration between student representatives from semesters I, III and V, totaling 16 students. The result of this activity is that students can create interactive student worksheets based on Google Forms.